Understanding the Attitudes of Communities to the Social, Economic, and Cultural Importance of Working Donkeys in Rural, Peri-urban, and Urban Areas of Ethiopia - Geiger, Martha; Hockenhull, Jo; Buller, Henry; Tefera Engida, Gebre; Getachew, Mulugeta; Burden, Faith Adelaide; Whay, Helen Rebecca (Frontiers in Veterinary Science, 2020)
Working donkeys (Equus africanus asinus) are vital to the development and support of people’s livelihoods in rural, peri-urban and urban areas of Ethiopia. However, despite their critical role in providing transport, food security and income generation to some of the poorest and most marginalized households, donkey contributions to human livelihoods have been largely unexplored. Donkey users, veterinary surgeons, business owners, and civil servants were interviewed to investigate the role humans play in shaping donkey lives while furthering our understanding of the social and economic impacts of working donkeys to human lives. Findings are discussed through seven guiding themes; donkeys as generators of income, the relationship between donkeys and social status, donkeys and affect, empowerment through donkeys, the role of donkeys in reducing vulnerability and encouraging resilience, donkey husbandry and gender dynamics all of which gave a broader and richer insight into the value of donkeys. Donkeys are an important support in rural, peri-urban and urban settings through the creation of economic security, independence and participation in local saving schemes. In addition, donkeys provide social status, empowerment to marginalized groups such as women and the very poor and provide a sense of companionship. Whether the interviewee was a donkey user or a key informant appeared to influence their views on donkeys and their welfare, as did their location. The variations in views and practices between urban and rural settings suggests that assessing the socioeconomic value of donkeys in different locations within the same area or country is critical, rather than assuming that similar views are held between compatriots. Despite their centrality to many people’s lives in Ethiopia, working donkeys often hold lowly status, are misunderstood, and given little husbandry and healthcare.